What are the likely causes of breast implant associated anaplastic large cell lymphoma (BIA-ALCL)?. (June 2022) - Lajevardi, Sepehr S.; Rastogi, Pratik; Isacson, Daniel; Deva, Anand K.
Abstract: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a CD30-positive, anaplastic lymphoma kinase-negative T-cell lymphoma. Where implant history is known, all confirmed cases to date have occurred in patients with exposure to textured implants. The etiopathogenesis of BIA-ALCL is likely to be multifactorial, with current evidence-based theories recognising the combination of chronic infection in setting of textured implants, gram-negative biofilm formation, chronic inflammation, host genetics (e.g. JAK/STAT, p53) and time in tumorigenesis. Proposed triggers for the development of malignancy are mechanical friction, silicone implant shell particulates, silicone leachables and bacteria. Of these, the bacterial hypothesis has received significant attention, supported by a plausible biological model. In this model, bacteria form an adherent biofilm in the favourable environment of the textured implant surface, producing a bacterial load that elicits a chronic inflammatory response. Bacterial antigens, primarily of gram-negative origin, may trigger innate immunity and induce T-cell proliferation with subsequent malignant transformation in genetically susceptible individuals. Future research, investigating BIA-ALCL genetic mutations and immunological modulation with Gram-negative biofilm in BIA-ALCL models is warranted to establish a unifying theory for the aetiology of BIA-ALCL.